Avaliação de um agroecossistema em transição agroecológica - Gonçalves, Larisse Medeiros (2020)
In view of the current deterioration offarming systems, it is believed that there are new forms of production that seek to balance agro-ecosystems, such as agroecology. The transition is a costly process, however, in the short term it can strengthen sustainability. From this, this work had as main objective to describe and understand the process of agroecological transition in an agroecosystem, what are the limitations and possibilities in the consolidation strategies of the process. For systematization, a compilation of methodologies has been devised to assist in a better understanding of agroecosystems and all its processes, such as the timeline, which seeks to know the family trajectory in the given agroecosystem. Agroecological zoning tools (edaphoclimatological survey, soil fertility analysis, georeferenced sketch with field description), the use of Participatory Rural Diagnosis (DRP) instruments as a seasonal calendar. For evaluation, parameters called Agroecological Transition Measurement Indicators (IMTA) were built, which make a diagnosis of what level of transition the agroecosystem is in. Through systematization, it can be seen that the main production crops are short-cycle vegetables and parsnip, which is a property differential. Changes in soil management and conservation influenced the change in pH and V%, decreasing Al3+, yet the insertion of poultry litter, even without formulation data, can promote soil fertility, contributing to the nutritional management of the soil. agroecosystem. The studied agroecosystem had an IMTA corresponding to 48.88%, which can be considered an agroecosystem with a high level of dependence, and improvements are needed to forward stability. If the research were carried out for another agricultural year, that is, at the end of the year 2020, IMTA would havefallen in value, as farmers showed that in January they already started dealing with some synthetic insecticides and will organize the procedure synthetic fertilization. The family did not reach the initial objective, which was to make the agroecological transition and build, through changes in management and technical itineraries, a more balanced and less dependent agro-ecosystem.